PENGARUH STRES KERJA DAN PERSEPSI KEADILAN ORGANISASIONAL TERHADAP TURNOVER INTENTION DENGAN MODAL PSIKOLOGIS SEBAGAI PEMODERASI - Rasistia Wisandianing Primadineska (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2021)
This study aimed to examine the moderating role of psychological capital (psycap) on the relationship between job stress and perceived organizational justice (distributive, procedural and interactional) towards the turnover intention. This study used a survey method both online and in-person and used public accountants who already work for 1-3 years as participants. The results showed that psychological capital able to moderate the impact of work stress and perceived organizational justice towards turnover intention. Auditors who have a good psychological capital can suppress his desire to move even though he faced the work stress and the perception of organizational justice that may not comply with his wishes. The results of the study also support the theory of positive organizational behavior which states that psychological capital is the main variable that affects individual motivation and performance.